2021
DOI: 10.1038/s41598-021-94488-8
|View full text |Cite
|
Sign up to set email alerts
|

In-silico design of envelope based multi-epitope vaccine candidate against Kyasanur forest disease virus

Abstract: Kyasanur forest disease virus (KFDV) causing tick-borne hemorrhagic fever which was earlier endemic to western Ghats, southern India, it is now encroaching into new geographic regions, but there is no approved medicine or effective vaccine against this deadly disease. In this study, we did in-silico design of multi-epitope subunit vaccine for KFDV. B-cell and T-cell epitopes were predicted from conserved regions of KFDV envelope protein and two vaccine candidates (VC1 and VC2) were constructed, those were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Simultaneously, it was observed that as antigen levels decreased, immunoglobulin levels increased. These outcomes confirm the effectiveness of the developed vaccine (Arumugam and Varamballi, 2021). The current spike protein-based multi-epitope subunit vaccine development showed promising results when analyzed through viroinformatics tools.…”
Section: Discussionsupporting
confidence: 67%
“…Simultaneously, it was observed that as antigen levels decreased, immunoglobulin levels increased. These outcomes confirm the effectiveness of the developed vaccine (Arumugam and Varamballi, 2021). The current spike protein-based multi-epitope subunit vaccine development showed promising results when analyzed through viroinformatics tools.…”
Section: Discussionsupporting
confidence: 67%
“…The multi-epitope vaccine's DNA sequence was generated and transformed to Escherichia coli expression system utilizing the Java Codon Adaptation Tool (JCat) platform. The vaccine expression in E. coli was measured through the codon adaptation index (CAI) and the vaccine's GC percentage 46 .…”
Section: Methodsmentioning
confidence: 99%
“…The vaccine construct was docked with a variety of immune cell receptors in order to determine how effective it will be in generating an immune response 47 . The vaccine's binding affinity was predicted in a blind docking study for TLR-4 (4G8A), MHC-I (1I1Y), and MHC-II (1KG0) receptors 46 . Using PatchDock 48 docking investigation was accomplished followed by FireDock server to refine the docked complexes 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The server delivers the codon adaptation index (CAI) (>0.8–1.0) and the GC content (30–70% in the output files to verify the transcription and translation efficiency of the planned vaccine construct [ 79 ]. Two restriction sites, EcoRI and BamHI, were inserted into the C and N terminals of the sequence, and SnapGene v5.0.8 software was employed to clone the modified sequence with the restriction site into pET-28a (+) plasmid obtained from SnapGene “ (accessed on 21 July 2022)” [ 80 ].…”
Section: Methodsmentioning
confidence: 99%